The Restless River : Yarlung Tsangpo-Siang-Brahmaputra-Jamuna - Pangare, Ganesh (World Bank, Washington, DC, 2021)
This report on the Yarlung-Tsangpo-Siang-Brahmaputra-Jamuna River Basin, is a first attempt at documenting the Brahmaputra as a one river system and presenting a multi-layered, holistic perspective of the entire river basin from the perspectives of the four riparian countries. The genesis of the report is the stakeholders from the riparian countries themselves, who highlighted the need for one comprehensive, fact-based document that provides information on the various aspects of the entire river basin and that comprehensively captures the viewpoints of those from all riparian countries. It was felt that a document of this type would be important for supporting the dialogue process and policy discussions on cooperative river basin management. It is natural to expect that such a document should be co-written by various stakeholders across the basin, along with other international experts. The authors are pleased that the report includes contributions from over ninety authors, which is a powerful expression of cooperation in and of itself. The report consolidates the existing wealth of knowledge and information on the river system. At its heart, however, are the riparian’s perspectives and insights that reflect how the river is deeply embedded in the cultures and the lives of the people living within it. The report portrays the inextricable interlinkages between those living in the countries that share the river system: even though they are divided by international borders, they are tightly connected through the basin’s water resources.